Preliminary analysis of the role of small hepatitis B surface proteins mutations in the pathogenesis of occult hepatitis B infection via the endoplasmic reticulum stress-induced UPR-ERAD pathway - Huang Chengrong; Zhang Hao; Wang Jing; Li Jianfei; Liu Qian; Zong Qiyin; Zhang Yunyun; Wang Qin; Zhou Qiang (Open Life Sciences)
A growing body of evidence has shown that hepatitis B surface antigen (HBsAg) mutations can influence the occurrence of occult hepatitis B infection (OBI), particularly amino acid substitutions in small hepatitis B surface proteins (SHBs). The mechanistic basis for these results, however, remains unclear. This study was designed to explore the potential impact and mechanisms of OBI-related SHBs mutations on serum HBsAg. Huh7 and HepG2 cells were transfected with plasmids encoding wild-type (WT) or OBI-related SHB mutation-containing sequences, after which a chemiluminescence approach was used to detect HBsAg levels in cell culture supernatants. Western blotting was further used to assess HBsAg and endoplasmic reticulum stress (ERS)-related protein levels in lysates prepared from these cells, while the localization of HBsAg within cells was assessed via immunofluorescent staining. Cells transfected with OBI-related SHB mutation-encoding plasmids exhibited lower supernatant HBsAg levels than cells transfected with WT plasmids. Intracellular and extracellular HBsAg levels in these mutant plasmid-transfected cells were lower relative to those for WT plasmid-transfected cells, and HBsAg accumulation within the ER was detected via immunofluorescent staining in cells transfected with OBI-related SHB mutation-encoding plasmids, ERS-related protein content was also significantly increased in mutant plasmid-transfected cells as compared to those in the WT group. These results suggest that proteins harboring OBI-related mutations may tend to accumulate in the ER, thereby triggering an ERS response and impairing the transcription and translation of HBsAg via the activation of the unfolded protein response and ER-associated protein degradation pathway. These effects ultimately reduce the overall assembly of HBV virions in the ER and their associated secretion.